Natya versus the Epic Literature - Gonc-Moačanin, Klara (Array, 1999)
Without the epic literature the classical theatre in India is unimaginable, just as it is in the ancient Greece or in the medieval Japan. The main Indian theoretical source on the classical theatre is the Natyasastra, which claims that the natya is the fifth Veda, just as the epics claim for themselves. The epics and the Harivamsa mention dramatic performances, but not the classical natya; it is mentioned in the younger puranic texts only. Prominent dramatists like Bhasa, Kalidasa, Bhavabhuti or Bhattanarayana often take their plots from the Sanskrit epics. The epics have influenced equally the younger forms of the dance drama.